(untitled) (Triyuga Academic Journal, 2024)
This paper explores the status of women in ancient Nepal during the Kirata and Lichhavi periods examining how the socio-economic framework, political systems, and cultural norms intersected to perpetuate gender inequalities. By analyzing published archives, including Sanskrit and Pali Buddhist religious texts, Vamshavalis, and Licchhavi inscriptions, the study reveals how patriarchal control was maintained and legitimized through laws and social practices. Except for the Khasa women kingdom of western Nepal, where there was matrimonial society, the broader societal framework systematically excluded women from political participation and economic autonomy. The caste system and early marriage customs further reinforced women’s subordination. This paper argues that the intersection of class and gender dynamics, driven by economic interests, played a crucial role in maintaining male dominance, unraveling the historical foundations of gender inequality in ancient Nepal. This study offers some valuable insights into the persistent system of gender oppression, informing contemporary discussions on women’s rights and social justice in Nepal that would encourage the future scholars to look into the issue from different perspectives for a holistic understanding of the condition of Ancient Nepali women.